Analysis of the effectiveness of energy strategies - Guliyev Igbal; Ruzakova Valeriya; Kuzmina Margarita (E3S Web of Conferences, 2023)
The article examines the effectiveness of national strategic energy planning within the context of countries’ adaptation to the global energy transition. The authors study the national energy strategies of the world’s 20 largest economies, with a particular focus on the technological aspects of adaptation to the global energy transition, and give analysis of their correspondence with the actual national performance.